A domino synthetic approach for new, angular pyrazol- and isoxazol-heterocycles using [DBU][Ac] as an effective reaction medium. Issue 30 (3rd March 2015) - Sutariya, Tushar R.; Labana, Balvantsingh M.; Parmar, Bhagyashri D.; Parmar, Narsidas J.; Kant, Rajni; Gupta, Vivek K.
Abstract : Some new, angular pyrazol- and isoxazol-heterocycles have been synthesized by the reaction of pyrazolone/isoxazolone with typical ketone-based substrates— O -alkenyloxy/alkynyloxy-acetophenones. Abstract : O -Cinnamyloxy/geranyloxy/cyclohexenyloxy/cinnamoyloxy-acetophenones yielded pyrazol-heterocycles, all of which contained an angular methyl-attached pyranopyran unit with pyrazolones in the ionic liquid (IL), 1, 8-diazabicyclo[5.4.0]undec-7-ene-8-ium acetate [DBU][Ac], via the domino/Knoevenagel-hetero-Diels–Alder (DKHDA) reaction. Besides, isoxazol yielded isoxazol-heterocycles possessing a framework to similar to O -allyloxy/prenyloxy-acetophenones, which did not involve chromatography to isolate the desired product. However, propargyl-substrates needed ZnO to promote the reaction. The heterosteroid-mimicking structure thus achieved may have different bioprofiles than the aldehyde-derived one. Moreover, the IL is recyclable and capable of promoting reaction effectively, which is indicative of an economical and greener way of achieving the interesting heterocycles. The stereochemistry of all the compounds was confirmed by 1 H NMR, 13 C NMR, 2D NMR NOESY and the single crystal X-ray diffraction data.